Pengaruh Suhu dan Waktu Penyangraian Terhadap Aktivitas Antioksidan dan Sifat Sensoris Kopi Tiruan Biji Pepaya (Carica papaya L.) - Najmudin, Najmudin; Sugitha, I Made; Pratiwi, I Desak Putu Kartika (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i03.p13, 2021)
This Study aims to determine the effect of temperature and roasting time on antioxidant activity and sensory properties of artificial coffee papaya seeds to produce papaya seeds coffee with high antioxidant activity and the best sensory properties. The experimental design used in this study was a Factorial Completely Randomized Design which were the first factor is the roasting temperature (80 o C, 90 o C, 100 o C) and the second factor is the roasting time (5 minutes, 10 minutes, 15 minutes). The treatment was repeated 2 times to obtain 18 experimental units. The data was analyzed with analysis of variance and if the treatment had a significant effect, then followed by Duncans Multiple Range Test. The parameters tested in this study included moisture content, total phenol, total flavonoid, qualitative caffeine, antioxidant activity and sensory properties. The results showed that papaya coffee seeds with a temperature of 100 o C and roasting time of 10 minutes were the best treatment with water content value of 3.76%, total phenol 1.25 mgGAE/g, total flavonoids 0.29 mgQE/g, antioxidant activity 24.03%, caffeine (qualitative) negative with sensory properties color was yellowish-brown, aroma was distintive of papaya seeds, taste was bitter, and overall acceptance was liked.